HBM4EU Chromates Study-Genotoxicity and Oxidative Stress Biomarkers in Workers Exposed to Hexavalent Chromium - Tavares, Ana (2022)
Funding: This project has received funding from the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement no. 733032 and received co-funding from the author’s organizations and/or Ministries.